Halitosis – what the ENT should know - Cunha, António Trigueiros (2022)
Halitosis defines as an unpleasant scent emanating from oral cavity beyond what is socially acceptable. It’s present in about 1/3 of the world population with clinical, psychological and social consequences. It is multifactorial, but it’s mainly related with oral pathology (80-90%). Other potentially causing etiologies of this condition are ENT pathologies (such as chronic rhinosinusitis or caseous chronic tonsillitis), respiratory pathology (such as cystic fibrosis or lung abscesses), gastrointestinal pathology (Gastroesophageal reflux or Zenker's Diverticulum), or even less commonly, upper aerodigestive tract neoplasms and systemic (chronic renal or hepatic failure) or metabolic (such as diabetic ketoacidosis or trimethylaminuria) pathology. The diagnosis can be performed through subjective tests, called organoleptic tests, or objective tests based on the quantification of the main compounds causing halitosis, the Volatile Sulfur Compounds (VSC). Treatment depends on its etiology. Therefore, oral hygiene is frequently recommended.